EP317 Efficacy of salvage hysterectomy following radiotherapy for uterine cervical adenocarcinoma. (1st November 2019) - Iwase, H; Sato, H; Endo, S; Furukawa, S; Ohnishi, K; Tazo, Y; Takada, T; Arai, M; Yoshino, O; Onda, T
Abstract : Introduction/Background: Treatment outcome of radiotherapy for uterine cervical adenocarcinoma (CA) is known to be poor compared with squamous cell carcinoma. Especially, the management for residual disease after radiotherapy remains unclear. The aim of this study is to evaluate the efficacy of salvage hysterectomy for residual disease after radiotherapy in patients with CA. Methodology: Medical records of 28 patients with CA who underwent radiotherapy or concurrent chemoradiotherapy (CCRT) as primary treatment at our hospital between 2004 and 2015 were retrospectively reviewed. Clinicopathological features and prognosis of these patients were analyzed. Fisher's exact test, Kaplan-Meier analysis, and Log-rank test were used for statistical analyses. Results: Median age was 59 years-old (range 36–87), and stage distribution was 3/10/12/3 in stage I/II/III/IV (FIGO 2008). Histology was adenocarcinoma in 23 and adenosquamous carcinoma in 5. Six patients received radiotherapy alone (RT) and 22 patients received CCRT (one with CDDP and 21 with CDGP as chemotherapy). Eleven patients (39.3%) achieved complete remission (CR) after RT or CCRT (RT-CR group). Five patients with residual disease in uterus and without other extra-uterine lesions achieved CR by means of salvage simple or modified radical hysterectomy following RT or CCRT (OP-CR group). Consequently, 16 patients achieved CR in total. Overall survival (OS) in CR group was significantly favorable compared with non-CR group (74.5% vs 24.2% in 2-year OS, p=0.006). Especially, patients in OP-CR group had excellent prognosis with an 80% 5-year OS, which was comparable with a 61.4% 5-year OS in RT-CR group. There was no significant difference in clinicopathologial features between CR and non-CR groups. Thus, there was no predictive feature for radiation effect. Conclusion: Salvage hysterectomy should be considered in patients with residual disease after radiotherapy, if they have no extra-uterine disease. Disclosure: Nothing to disclose.